Purification and properties of asparaginase from the testa of immature seeds of pea (Pisum sativum L.) - Chagas,Eliana P. (2001)
A K+-dependent asparaginase (E.C. 3.5.1.1.) was purified 1328-fold from the testas of immature pea seeds (Pisum sativum L., var. Bolero) and characterized. Antibodies raised against purified asparaginase cross-reacted with the putative asparaginase band in Western blot analyses of semi-purified extracts. However, for crude extracts of pea testas, a cross-reaction was obtained with at least four protein bands, one of which was asparaginase protein. Affinity-purified antibodies to the four strongest bands of crude extracts were fairly specific for the bands from which they were purified, suggesting a mixture of specific antibodies. The Mr of asparaginase was 69,000 by Sephacryl S200 chromatography and also by mobility on native PAGE relative to BSA. There was no evidence for dissociation into subunits on SDS-PAGE, suggesting a monomeric protein of Mr 69,000. Other properties include an apparent Km of 2.4 mM, pI between 4.5 and 5, and competitive inhibition by aspartate and glycine.